ANGER EXPRESSION AND PARENT-CHILD RELATIONSHIP AMONG ADOLESCENTS: MEDIATING ROLE OF SELF ESTEEM - Babar, Aneeza; Saleem, Sadia; Ayub, Sumaira (Journal of Pakistan Psychiatric Society, 2022)
Objectives: The present study explored the relationship between anger expression, self-esteem, and parent-child relationship among adolescents also the mediating role of self-esteem influencing the relationship between anger expression and parent child relationship among adolescents. Research design: It was a correlational research design. Subjects and Methods: The sample comprised 479 adolescents of age range 10 to 18 years with mean age 13.87+ 1.53 years including 239 (50%) boys and 240 (50%) girls. The data was collected from four different government schools of Lahore by employing convenient sampling techniques. The Anger Expression Scale for Adolescents (AESA) (Babar & Saleem, 2012), Parent-Child Relationship Scale (PCRS) (Mahmood, Ijaz & Saleem, 2011), Self Esteem Scale for Children (SESC) (Mahmood & Saleem, 2011) were used for assessment. Results: The results showed that anger expression is negatively related with self-esteem and closeness in parent child relationship, while positively related with rejection and distant parent child relationships. Results also showed that self-esteem is a positively related closeness aspect of parent child relationship. The results of Mediation through PROCESS macro showed a significant mediating role of self-esteem in determining the relationship between anger expressions and parent-child relationship (closeness, rejection and distant) among adolescents. Conclusion: The mediating role of self-esteem in anger expression and parent-child relationship highlighted in the present study. This study has a major contribution in the field of counseling psychology specifically focusing on the adolescent’s behavioral problem highlighting the significant role of parental relationship in their lives and resulting behavioral issues.